Facing Up to the American Dream : Race, Class, and the Soul of the Nation. - Hochschild, Jennifer L. (Princeton University Press, 2001)
The ideology of the American dream--the faith that an individual can attain success and virtue through strenuous effort--is the very soul of the American nation. According to Jennifer Hochschild, we have failed to face up to what that dream requires of our society, and yet we possess no other central belief that can save the United States from chaos. In this compassionate but frightening book, Hochschild attributes our national distress to the ways in which whites and African Americans have come to view their own and each other's opportunities. By examining the hopes and fears of whites and es.